Implementasi Nilai Exposure Index dan Indeks Massa Tubuh dalam Pemilihan Parameter Sistem Automatic Exposure Control Pada Radiografi Toraks (Studi Kasus Pada Rumah Sakit Universitas Andalas) - Yulma Susanto, Riyan; Adrial, Rico; Milvita, Dian; Oktavia, Amel (Universitas Andalas, 2025)
This study aims to analyze the application of EI (Exposure Index) values to evaluate exposure indications in thorax PA examinations. It also examines the influence of patient BMI (Body Mass Index) on parameter selection, such as estimated body size in the AEC (Automatic Exposure Control) system. Data collection was conducted on patients aged 15-73 years undergoing thorax PA examinations using the AEC system. The data collected included patient mass (kg), height (m), selected estimated body size on the AEC system, exposure factor values (source voltage (kV)), and EI values. The method used to evaluate the implementation of EI values involved comparing the EI values from the examinations with the vendor-recommended EI values for CR (Computed Radiography) to determine the resulting exposure indications. Furthermore, the influence of BMI on parameter selection in the AEC system was analyzed using a simple linear correlation test to determine the correlation between BMI values and the resulting EI values. The study results showed that thorax PA examinations using the AEC system produced optimal exposure indications in 57% of cases and underexposure indications in 43% of cases. Causes of underexposure indications included the selection of exposure factors that were not fully adjusted to the patient's physical condition based on BMI values, delay time processing on the imaging plate, and the use of collimation fields exceeding diagnostic needs in some examinations. BMI values showed a significant correlation with EI values.